Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Perusahaan (Studi Kasus Pada PT Niaga Nusa Abadi Depo Bima) - Dwi Wulandari; Dwiyani Sudaryanti; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study is to test the effect of the internal control system accounting information system on the company's performance. The sample in this study was 25 respondents, with a total population of 113 PT employees. Niaga Nusa Abadi Bima Depot. The sampling technique in this study used the Purposive sampling Method, using primary data from the distribution of questionnaires which were then analyzed by an analysis method in the form of multiple linear regression analysis with the SPSS statistical program version 25. The results of the research show that the accounting information system and internal control system have a positive effect on the company's performance.Keywords: Accounting information system, internal control system and company performance